Pengaruh Fasilitas, Harga Tiket, dan Kualitas Film Terhadap Minat Beli Penonton Movimax Mall Dinoyo Kota Malang - Putri, Fiona Hananto; Wahono, Budi; Hardaningtyas, Ratna Tri (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract The study aims to find out the impact of the facilities, ticket prices, and quality of the film on the interest of the Movimax Cinema Audiences in Purchasing Poor Cities. The location of the research was carried out Movimax Dinoyo, Dinoyo Mall Lt. 4, M.T. Haryono Road No. 195, Lowokwaru, Lowokvaru district, Malang City. Phone number (0341) 5022949. This research is quantitative. In this study, the non-probability sampling technique is used with the judgmental samplings category, which means that visitors who fill in the questionnaire must meet the existing criteria. The number of samples was determined using Roscoe's formula and resulted in 40 respondents. The data was analyzed using a double linear regression test and a determination test. Based on the data analysis, the test results showed that facilities, ticket prices, and movie quality partially had a significant positive influence on the audience's interest in Movimax Poor City Cinema purchases. The determination test results indicated that a percentage of 66.4% indicates that audience purchasing interest was influenced by the facility, ticket price, and film quality. Keywords: Facilities, Ticket Price, Film Quality, Audience Interest